Complexity of small-scale commercial area on Menoreh Street in Semarang and its contribution to trip attraction model. Issue 1 (May 2021) - Basuki, Y; Rahayu, S; Andrika, A F
Abstract: The various small-scale commercial create complexity in estimating the travel impact, especially the congestion on collector roads that connect city center and sub-city center. The purpose of this study is to understand the complexity of commercial land use through trip attraction model and its contribution to traffic flow on Menoreh Street as one of the collector roads in Semarang City. The method that used are contribution trip attraction by classification of small-scale commercial activities and multiple linear regression with dependent variable Y is the trip attraction of small-scale commercial area (pcu/hour) and the independent variables are X1 (store area), X2 (parking area), X3 (sales income), X4 (number of employees), and X5 (store operational hours). There are thirteen classification which apparel store has a biggest contribution and car wash has a lowest contribution to trip attraction. From that classification, there are five different model which number of employees and sales income influence the trip attraction. The model can estimate trip attraction in the small-scale commercial area that is growing rapidly in the Semarang City so that it can anticipate the transportation problems.